Child homicide: generating victim and suspect risk profiles. Issue 3 (3rd August 2015) - Roach, Jason; Bryant, Robin
Abstract : Purpose: – In England and Wales, on average one child every week is a victim of homicide. The purpose of this paper is to explore whether different victim-risk profiles and suspect variables can be differentiated for specific victim ages. Design/methodology/approach: – This paper presents a preliminary analysis of more than 1, 000 child homicides committed in England and Wales between 1996 and 2013, from data provided through the Homicide Index. Statistical techniques such as cluster analysis were used to identify specific victim-risk profiles and to analyse suspect variables according to the age of victim. Findings: – The findings present a clearer picture of the risk-age relationship in child homicide, whereby several specific risk profiles are identified for specific child ages, comprised of crime variables including; likely victim and suspect demographics, the most likely circumstances of the homicide and methods of killing. Using similar techniques, a number of tentative clusters of suspects implicated in child homicide are also described and analysed, with suggestions of further analysis that might prove of value. Practical implications: – The practical implications cannot be understated. For those professionals working in the fields of child protection and criminal investigation the identification of risk profiles promises to provide a back-cloth with which to practice when confronted with complex and distressing child homicide scenarios. This research promises most to those currently training in related professions. Originality/value: – Although the statistical level of risk has been linked with the age of a child (with younger children being most vulnerable to killing by a parent or step-parent and older children most vulnerable to killing by acquaintances and strangers), extant research is yet to progress beyond the identification of broad age-risk categories. The paper concludes with a discussion of the likely implications for those charged with reducing and investigating child homicide and outlines the possibility of future research.